PENGAYAAN MODUL BIOLOGI SMK PERTANIAN KELAS XI PADA POKOK BAHASAN PEMANFAATAN LIMBAH PELEPAH KELAPA SAWIT UNTUK PEMBUATAN BRIKET ARANG - Ramadhan, Syahrul Ramadhan; Marhadi, Imam Mahadi; Wulandari, Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: There have been experimental studies to examine the use of oil palm fronds waste to raw material for charcoal briquettes and the results of this study can be used as an enrichment of teaching materials in the form of vocational biology modules on the subject of the utilization of waste. This study was conducted from March to June 2015. The method used in this study is an experiment using a completely randomized design (CRD) with 4 treatments performed 5 times repeat the treatment given is as follows (1) Charcoal oil palm fronds non sieve (B0), (2) Charcoal midrib palm oil is refined by sieve size of 30 mesh (B1), (3) Charcoal palm fronds were mashed with a 50-mesh sieve (B2), (4) Charcoal palm fronds were smoothed with a sieve size of 70 mesh (B3). Parameter studies that measured the water content, ash content, levels of substance evaporates, the density and firmness press. Treatment with a 70 mesh sieve (B3) to be most successful for the manufacture of charcoal briquettes compared to the treatment of non sieve (B0), treatment with 30 mesh sieve (B1) and treated with a 50 mesh sieve (B2). Treatment with a 70 mesh sieve (B3) produces 8% moisture content, ash content of 8.4%, 14.8% levels of substance evaporates, the density of 0.94 g/cm3, and firmness press 61.80 g/cm3. The results could be used as an enrichment module for vocational subjects Biology Class XI. This study is expected to continue at the stage of implementation and evaluation of the ADDIE model of instructional development. Keywords: Enrichment Module, Waste Utilization, oil palm fronds, Charcoal Briquettes